The Impact of Pedestrian Crossings on Speed Patterns and Roundabout Capacity - Ayoub Charef; Zahi Jarir; Mohamed Quafafou (International Journal of Scientific Research and Innovative Studies, 2024)
This study investigates how pedestrian crossings impact both the speed dynamics and capacity of roundabouts, aiming to optimize traffic flow. Pedestrians traditionally hold priority at unsignalized intersections and roundabouts, significantly affecting operational efficiency. The paper underscores the pivotal role of crosswalk placement in mitigating disruptions to vehicular flow and preventing congestion. Data for this research were gathered from roundabouts in Marrakech, Morocco, utilizing mobile phones to track vehicle and pedestrian volumes, as well as passage times. In addition to field data, Vissim simulations were employed to enhance accuracy. Our study specifically delves into the impact of pedestrians on roundabout exit lane capacity. The primary goal is to identify the ideal distance between roundabouts and crosswalks to maximize capacity. The findings provide valuable insights for urban planning and traffic management, addressing the dynamic interaction between pedestrian flow, crosswalk positioning, and overall roundabout efficiency. Key words: roundabout entry capacity, pedestrian crossings, yolo detection, traffic streams analysis, VISSIM simulation.